Permainan Daring sebagai Medium Penyebaran Hate Speech: Dampaknya terhadap Anak dan Strategi Penanggulangannya dalam Perspektif Ilmu Komunikasi - hubbah, zahratul - (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2025)
This study aims to analyze the phenomenon of hate speech dissemination in online games, its impact on children's communication behavior, and mitigation strategies from a communication science perspective. The research was motivated by the growing prevalence of hate speech in digital environments accessed by children. The study employs Computer-Mediated Communication (CMC) theory, the concept of hate speech, and communication strategy frameworks. A qualitative approach was used through literature review methods. The subject of the study is the hate speech phenomenon in online games, while the object is its effect on children's communication behavior. Secondary data were collected from academic journals, research reports, and media coverage. Content and thematic analysis techniques were applied within the critical tradition of communication studies. The findings indicate that hate speech in online games is driven by factors such as anonymity, permissive gaming community culture, and weak content moderation. The impacts include adoption of aggressive language, emotional desensitization, and development of discriminatory attitudes among children. Recommended mitigation strategies highlight the need for reflective communication, digital literacy education, and collaboration between parents, teachers, and platform developers.